(untitled) (Bangladesh Journal of Public Administration, 2022)
2020 was not an easy ride since the COVID-19 pandemic wreaked havoc on economies and dragged around 120 million people into the pit of poverty and despair. Although the pandemic posed daunting challenges to its final fight against poverty, China fulfilled its promise of eradicating extreme poverty by the end of 2020 as scheduled. This article reviews China’s achievements in poverty alleviation, and examines how and why China can end extreme poverty by adopting targeted poverty alleviation. The context that is characterized by economic restructuring, regional disparity and income inequality calls for individualized attention to people in poverty. Thus, the strategy of targeted poverty alleviation was introduced to push forward poverty elimination in China by reaching the poor. To roll out the strategy nationwide, China identified all the poor households by door-to-door investigation, dispatched officials to the frontline of poverty eradication, and conducted wide-scale and multi-faceted evaluation of the poverty elimination results. In addition, multi-pronged anti-poverty measures are introduced, which include infrastructure, developing local industries, relocation, eco-compensation, education, social security and special initiatives for vulnerable groups. At the end of the article, future challenges and formidable obstacles are listed. Findings suggest that China should start focusing on the people who may slip back into poverty, on the urban poor and on regional inequality. This is a review and analysis has been done based on the available secondary sources of data collected from government publications, research articles, and international organization statistics.